2014
DOI: 10.1504/ijiq.2014.068656
|View full text |Cite
|
Sign up to set email alerts
|

A classification of data quality assessment and improvement methods

Abstract: Data quality (DQ) assessment and improvement in larger information systems would often not be feasible without using suitable "DQ methods", which are algorithms that can be automatically executed by computer systems to detect and/or correct problems in datasets. Currently, these methods are already essential, and they will be of even greater importance as the quantity of data in organisational systems grows. This paper provides a review of existing methods for both DQ assessment and improvement and classifies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…As recommender systems are an important category of decision support systems (Power et al 2015), this research is in line with recent works which have revealed a significant impact of data quality dimensions, especially completeness, on data-driven decision support systems (e.g., Feldman et al 2018;Heinrich et al 2019;Woodall et al 2015).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…As recommender systems are an important category of decision support systems (Power et al 2015), this research is in line with recent works which have revealed a significant impact of data quality dimensions, especially completeness, on data-driven decision support systems (e.g., Feldman et al 2018;Heinrich et al 2019;Woodall et al 2015).…”
Section: Introductionsupporting
confidence: 86%
“…Mladenić and Grobelnik 2003;Vanaja and Mukherjee 2019), as different data sets (e.g., with more or fewer attributes) may lead to varying results of decision support. Thus, the impact of the data quality of data values on different evaluation criteria of decision support systems such as decision quality or data mining outcome has been studied in existing literature (e.g., Bharati and Chaudhury 2004;Blake and Mangiameli 2011;Feldman et al 2018;Ge 2009;Heinrich et al 2019;Woodall et al 2015). Yet, this research neither focuses on how to systematically achieve more complete item content data sets nor on how to define a wellfounded procedure, but instead tries to explain the relationship between data quality and evaluation criteria of decision support systems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the data extraction process is perfect, if the data from the source systems contains errors, then these will propagate to the DT. There are, however, certain types of these errors that can be detected and corrected in the transformation process, such as incorrectly formatted data and invalid data (Woodall et al 2014). DTs may utilise publicly available online data in the city level, such as using weather forecasts etc.…”
Section: Analysis Of the Dts Development From The Perspective Of Data Managementmentioning
confidence: 99%
“…At the contrary, most of these methods are focused on DQ assessment or improvement in isolation. Similar to the mentioned review, a most recent study developed by Woodall et al [ 33 ] classified most recent DQ assessment and improvement methods. This work suffers the same problem than the work of Batini et al Apart of these methodologies, there is a lack of comprehensive methodologies for the assessment and improvement of DQ in the domain of SCP operations and their underlaying data.…”
Section: Related Workmentioning
confidence: 99%